Domesticated mammoths : Mythic and material in Nenets verbal tradition on ya’ xora - Lukin, Karina (Multilingua, 2022)
This article discusses language materialities and the Otherworld through the findings of mammoth remains and text-artifacts representing Nenets verbal art. The remains and verbal art are read together as a network of mythic knowledge that forms a semiotic whole, where different signs interact and create potentials for new significations. The article aims to open up a web of relations in which materialities of differing ages and durabilities meet and affect each other through their semiotic potentialities. The materialities operate on several levels of signification, ranging from basic metaphors for mammoths to larger regimes that organize the signification. Consequently, mythic knowledge concerns worlds that are, on the one hand, imperceptible but, on the other, sensible through narration and imagination in terms of materialities. The key material elements of the mythic knowledge are tainted by the narration, such that they cannot be considered without the mythic qualities. In addition, the knowledge concerning the world affects Nenets rituals and ways of dwelling. Peer reviewed